Perspectives of Nahdlatul Ulama (NU) and Muhammadiyah Figures on Law of Buying and Selling Breast Milk (ASI) - Al Munawar, Faishal Agil; Putri, Febi Ananda (Journal of Modern Islamic Studies and Civilization, 2024)
The buying and selling of breast milk (ASI) transactions are based on the ignorance of the society, especially mothers, regarding the prohibition of buying and selling breast milk. Nahdlatul Ulama and Muhammadiyah, as community organizations in Indonesia, have also discussed determining the law regarding the practice of donating and buying breast milk. Therefore, the aim of this research is to understand the mechanism of buying and selling breast milk and the perspectives of Nahdlatul Ulama and Muhammadiyah figures on the law of buying and selling breast milk. This research is an empirical juridical study using a qualitative approach with a descriptive comparative method. The results of this study show that the practice of buying and selling breast milk is conducted through the social media platform Facebook. Buying and selling are done using a barter method based on the needs of the baby. According to Nahdlatul Ulama and Muhammadiyah, both bartering and cash transactions fall under the same law. Breast milk as an object essentially meets the requirements of a saleable object. However, there is an opinion that breast milk is equated with human organs, thus buying and selling breast milk is prohibited as per the law against selling organs. Nahdlatul Ulama believes that buying and selling breast milk is permissible, referring to the respected Shafi'i opinion that it is valid and permissible. However, if there are government regulations prohibiting the buying and selling of breast milk, the society must adhere to those regulations. Meanwhile, Muhammadiyah has not yet discussed the issue of buying and selling breast milk. The discussions conducted so far have only touched upon the permissibility of breast milk donation, which is done voluntarily.